Quantum stochastic processes: boson and fermion Brownian motion - Kobryn, A.E.; Hayashi, T.; Arimitsu, T. (Condensed Matter Physics, 2003)
Dynamics of quantum systems which are stochastically perturbed by linear coupling to the reservoir can be studied in terms of quantum stochastic differential equations (for example, quantum stochastic Liouville equation and quantum Langevin equation). In order to work it out one needs to define the quantum Brownian motion. As far as only its boson version has been known until recently, in the present paper we present the definition which makes it possible to consider the fermion Brownian motion as well.